2021
DOI: 10.3390/pharmaceutics13091473
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Conductivity of Alginate Hydrogels Containing Reduced Graphene Oxide through the Addition of Proteins

Abstract: Modifying hydrogels in order to enhance their conductivity is an exciting field with applications in cardio and neuro-regenerative medicine. Therefore, we have designed hybrid alginate hydrogels containing uncoated and protein-coated reduced graphene oxide (rGO). We specifically studied the adsorption of three different proteins, BSA, elastin, and collagen, and the outcomes when these protein-coated rGO nanocomposites are embedded within the hydrogels. Our results demonstrate that BSA, elastin, and collagen ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 78 publications
(108 reference statements)
1
8
0
Order By: Relevance
“…In addition, the equilibrium constant ( K 2 ) reveals an inverse dependency with the sample’s hydrophilicity, since it was found that it decreases for samples with functionalized surfaces. This has been reported previously for OCFG functionalized biomaterials [ 53 ].…”
Section: Resultssupporting
confidence: 85%
“…In addition, the equilibrium constant ( K 2 ) reveals an inverse dependency with the sample’s hydrophilicity, since it was found that it decreases for samples with functionalized surfaces. This has been reported previously for OCFG functionalized biomaterials [ 53 ].…”
Section: Resultssupporting
confidence: 85%
“…As a consequence of its ability to bond with diverse biomolecules such as DNA, proteins, and antibodies, it has been used as drug delivery system, protein carrier or biosensor component. [ 29,30 ] In tissue engineering fields, it has been reported to favour osteogenic differentiation of cells and to supply the hydrogels with excellent mechanical properties. [ 17 ] In a previous study, it was concluded that the 50 µg mL −1 of GO was the best concentration for cell viability and functionality in Alg microcapsules.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, mediator-less conductance measurements enabling direct comparisons with the above-mentioned were not made. Graphene oxide (GO), reduced graphene oxide (RGO) and MWCNT have been used to modulate hydrogel conductivity ( Golafshan et al, 2017 ; Liu et al, 2018 ; Serrano-Aroca et al, 2018 ; Fu et al, 2019 ; Li et al, 2019 ; McNamara et al, 2020 ; Raslan et al, 2021 ). While RGO and MWCNT are hydrophobic and GO is hydrophilic, all nanomaterials have exhibited the same level of teratogenicity in zebrafish ( Liu et al, 2014 ; Shu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…While RGO and MWCNT are hydrophobic and GO is hydrophilic, all nanomaterials have exhibited the same level of teratogenicity in zebrafish ( Liu et al, 2014 ; Shu et al, 2020 ). Relevant cyclic voltammetry studies range from optimal design of fiber-based capacitors the volumetric capacitance of MWCNT was approximately quadrupled for an RGO/MWCNT mixture (4 F cm −3 ) ( Raslan et al, 2021 ) to mediated enzymatic reactions where chitosan and graphene were blended to measure metabolic activity ( Feng and Wang, 2021 ). However, neither of the studies above emulate the nanocomposite stacking, diffusion limitations and the potassium hexacyanoferrate (II)/(III) complexes mediated conditions used in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation